Analisis Pengaruh Faktor Sosial dan Pengalaman Terhadap Kepercayaan Untuk Meningkatkan Keputusan Pembelian Customer to Customer (C2C) E – Commerce di Semarang - Wibowo, Bayu Agung; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2016)
Along with its development, is currently the Internet could be used as a business tool. Business over the Internet, known as E-Commerce has been growing rapidly in Indonesia, one of which Customer to Customer (C2C) E-Commerce. E-commerce become more modern shopping models and start favorite by consumers in Indonesia because it is not limited by distance and time. This study aims to investigate the influence of social factors and the experience of the trust and its impact on the purchase decision Customer to Customer (C2C) E-Commerce. This research hypothesis testing using the data of 200 respondents. The analysis technique used in this research is Structural Equation Modeling (SEM) with AMOS 22. From the test results are known hypothesis that the experience had a positive and significant impact on the trust and is the most influential variable on trust. Then trust positive and significant impact on purchasing decisions. It supports previous research that trust is an important factor in the purchase decision Customer to Customer (C2C) E-Commerce.